Structural integrity analysis of notched ferritic steels operating within their ductile-to-brittle transition zone: An approach from Failure Assessment Diagrams and the Notch Master Curve. (December 2015) - Cicero, S.; García, T.; Madrazo, V.
Abstract: This paper provides a structural integrity assessment methodology for the analysis of ferritic steels containing notch-type defects and operating within their ductile-to-brittle transition zone. The methodology, based on the use of Failure Assessment Diagrams and the novel concept of the Notch Master Curve, has been applied to 323 experimental results performed on four different steels (S275JR, S355J2, S460M and S690Q), six different notch radii (from 0 mm up to 2.0 mm), two different types of specimens (CT and SENB), and three different temperatures within the corresponding ductile-to-brittle transition zone. The results validate the proposed assessment methodology. Highlights: We propose an assessment methodology for notched ferritic steels within the DBTZ. It is based on the use of Failure Assessment Diagrams and Notch Master Curve. It has been applied to 323 experimental results performed on four different steels. The results validate the proposed assessment methodology.